2019
DOI: 10.1093/brain/awz327
|View full text |Cite
|
Sign up to set email alerts
|

The structural connectivity of discrete networks underlies impulsivity and gambling in Parkinson’s disease

Abstract: See O’Callaghan (doi:10.1093/brain/awz349) for a scientific commentary on this article. Mosley et al. examine impulsivity and naturalistic gambling behaviours in patients with Parkinson’s disease. They link within-patient differences to the structural connectivity of networks subserving reward evaluation and response inhibition, and reveal pivotal roles for the ventral striatum and subthalamic nucleus within these networks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
42
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 103 publications
6
42
2
Order By: Relevance
“…For instance, ICD has been associated with increased connectivity between the left subthalamic nucleus and the left parietal operculum, whereas trait impulsivity has been associated with a weak connectivity between the left putamen and the right inferior temporal gyrus 21 . Other studies investigating cortical thickness, tractography, or functional MRI have also reported inconsistent results [5][6][7][19][20][21][22] . One of the causes is that impulsivity contains multifaceted constructs.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…For instance, ICD has been associated with increased connectivity between the left subthalamic nucleus and the left parietal operculum, whereas trait impulsivity has been associated with a weak connectivity between the left putamen and the right inferior temporal gyrus 21 . Other studies investigating cortical thickness, tractography, or functional MRI have also reported inconsistent results [5][6][7][19][20][21][22] . One of the causes is that impulsivity contains multifaceted constructs.…”
mentioning
confidence: 98%
“…High impulsivity (HI) is a precursor of ICDs and can also lead to severe ICDs 18,19 . While HI may be within the spectrum of ICDs, the underlying pathophysiological mechanism differs between trait impulsivity and ICDs 20 . For instance, ICD has been associated with increased connectivity between the left subthalamic nucleus and the left parietal operculum, whereas trait impulsivity has been associated with a weak connectivity between the left putamen and the right inferior temporal gyrus 21 .…”
mentioning
confidence: 99%
“…The emergence of ICD during dopamine replacement therapy on patients with PD has been attributed to two neurocognitive mechanisms ( Mosley et al, 2019 , Paz-Alonso et al, 2020 , Cilia and van Eimeren, 2011 ). The first mechanism consists of functional alterations in the reward system, especially the ventral striatum (VS), which may alter reward valuation.…”
Section: Introductionmentioning
confidence: 99%
“…Functional alterations in the inhibitory network constitute a second neurocognitive mechanism, which may contribute to abnormal impulsivity ( Mosley et al, 2019 , Paz-Alonso et al, 2020 ). Impulsivity is broadly seen as a failure of inhibition and is commonly divided into a “motor” subtype related to the failure to inhibit inappropriate actions and a “cognitive” subtype related to e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation